A model for optimizing the learning of basic techniques of fight in standing position for young judokas - Pimenovs, E.; Fernate, A.; Pimenovs, A. (LASE Journal of Sport Science, 2022)
The growing popularity of judo around the world is forcing researchers and coaches to constantly look for new, effective, and scientifically based tools and methods for learning judo techniques for optimal competition performance. The opinions of judo specialists on mastering the judo technique are divided into two groups: one believes that a smaller amount of technique should be taught, and that the focus should be on mastering these techniques better, while the other believes that the basics of technical training are the acquisition of basic techniques, i.e., the acquisition of 40 techniques. Increasing the efficiency of the training process with a well-thought-out set of tools and methods is an important condition for mastering the basic techniques of fight in standing position in judo. The research aim is the approbation of the model for optimizing the learning of basic techniques of fight in standing position for young judokas. Research methods: research and analysis of literature sources, expert evaluation method, modelling, observational experiment, and mathematical statistics. The research involved judokas aged 7-12 (58 judokas) and 3 judo experts. The research results reveal that the model for optimizing the acquisition of basic techniques of fight in standing position in judo consists of identifying the learning needs of judokas; setting learning goals; setting learning tasks; choice of learning methods and tools; assessment of learning results, as well as general developmental, auxiliary exercises, and special developmental and competition exercises. The optimization of learning the basic techniques of fight in standing position in judo is initially done by using general developmental, auxiliary exercises, special development, and competition exercises, during which the elements of the technique are mastered up to the skill level, followed by 5 student grades (kyo) with 8 techniques in each. The experience of accumulated movements is expanded, and body movements are managed in 3 planes, as well as physical properties are developed in parallel, with an emphasis on coordination skills.